1995
DOI: 10.1007/bf02245810
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the kappa agonist U-50,488 on cocaine-induced conditioned and unconditioned behaviors and Fos immunoreactivity

Abstract: The ability of kappa opioid agonists to modulate dopamine-mediated behavior and Fos immunoreactivity was assessed in adult rats. It was predicted that kappa agonist treatment would block the unconditioned and conditioned behaviors produced by cocaine (an indirect dopamine agonist). In the initial experiments, cocaine-induced locomotor activity was assessed after either acute or chronic injections of the kappa receptor agonist U-50,488 (5 mg/kg, SC). As expected, U-50,488 decreased cocaine-induced activity, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 31 publications
12
105
1
Order By: Relevance
“…1991;Moratalla et al 1992;Bhat and Baraban 1993; McGinty 1994, 1995;Fosnaugh et al 1995;Tan et al 2000;Grimm et al 2003;Le Foll et al 2005;Fumagalli et al 2006). Furthermore, cocaine-associated cues activate IEGs (Brown et al 1992;Crawford et al 1995;Everitt and Robbins 2000;Ciccocioppo et al 2001;Thomas et al 2003). Most relevant to the present study, re-exposure to an environment previously associated with cocaine self-administration, with or without a priming injection following prolonged cocaine abstinence, resulted in enhanced Fos protein expression within the anterior cingu-late, nucleus accumbens, basolateral amygdala, hippocampal formation, and central grey (Neisewander et al 2000).…”
mentioning
confidence: 55%
“…1991;Moratalla et al 1992;Bhat and Baraban 1993; McGinty 1994, 1995;Fosnaugh et al 1995;Tan et al 2000;Grimm et al 2003;Le Foll et al 2005;Fumagalli et al 2006). Furthermore, cocaine-associated cues activate IEGs (Brown et al 1992;Crawford et al 1995;Everitt and Robbins 2000;Ciccocioppo et al 2001;Thomas et al 2003). Most relevant to the present study, re-exposure to an environment previously associated with cocaine self-administration, with or without a priming injection following prolonged cocaine abstinence, resulted in enhanced Fos protein expression within the anterior cingu-late, nucleus accumbens, basolateral amygdala, hippocampal formation, and central grey (Neisewander et al 2000).…”
mentioning
confidence: 55%
“…Results indicated, however, that the magnitude of Mn-induced toxicity in the nucleus accumbens, and other relevant brain regions, was apparently insufficient to impair performance on the CPP task. Additionally, CPP performance has been reported to vary according to sex, with female rats and mice showing more robust place preferences than males (Russo et al, 2003;Balda et al, 2006; but see Crawford et al, 1995;Campbell and Spear, 1999). For this reason we included both sexes in the CPP experiment but found that (a) Mn did not differentially affect place preference conditioning of male and female rats, and (b) preference testing and reinstatement performance did not differ according to sex (perhaps due to insufficient n).…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of kappa receptor agonists with cocaine has been shown to attenuate the rewarding and behavioral effects of cocaine. Pretreatment with kappa agonists has been shown to decrease self-administration of cocaine (Glick et al 1995;Mello and Negus 1998;Negus et al 1997;Schenk et al 1999), cocaine place preference (Crawford et al 1995;Schenk et al 1999), locomotor sensitization (Schenk et al 1999), and cocaine-induced reinstatement (Schenk et al 1999(Schenk et al , 2000. These findings have led to the hypothesis that cocaine self-administration could be attenuated by pretreatment with kappa agonists.…”
Section: Clinical Implications Of Kappa Antagonism On Drug Reinstatementmentioning
confidence: 99%